Penataan Permukiman Padat di Kelurahan Kalukuang, Kota Makassar - Herlina Syam; Shirly Wunas; Yusni Mustari (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2015)
Housing and settlements began to develop rapidly in functional areas, especially in the city of Makassar. Land use problems basically arise due to the absence of clear and precise references in determining the location or land for buildings. This problem occurs in the Kalukuang Village area which is one of the new business center areas or the Central Business District (CBD). This area has developed quite rapidly due to its strategic location in the middle of the city. The purpose of this study is, to determine the condition of housing development patterns, the condition of facilities and infrastructure, analyze the driving factors and pull factors, and compile the residential housing structuring concept in Kalukuang Village. The analytical method used is descriptive and exploratory qualitative analysis, quantitative analysis and needs analysis. The results of this study indicate the development of settlements in the Kalukuang Village following a road network pattern in the form of a grid pattern. Some of the available facilities and infrastructure already meet the standards for example, educational facilities, worship, road infrastructure, and others. The driving factor affecting the development of settlements is a strong kinship factor and available residential land. Meanwhile, the pull factors are near work location, low transportation costs, complete facilities and infrastructure, and strong psychological factors. The concept of settlement arrangement is in the form of settlement patterns, namely, grid patterns in zones 1 and 2, centralized patterns in zones 3, 4, and 5. In addition, a waste management and road improvement system is also planned.